The Future of Indonesian Food Consumption - Bustanul Arifin; Noer Azam Achsani; Drajat Martianto; Linda Karlina Sari; Ahmad Heri Firdaus (Jurnal Ekonomi Indonesia, 2019)
This study aims to develop a model of the future of Indonesia’s food consumption up to 2045, using a baseline of food consumption in 2017 and projections to 2025 as milestones, and to draw policy relevance on food and related issues for the next Medium-Term Development Planning of 2020–2024. The projected demand of Indonesian food consumption is built based on the functional relationship between income and food consumption at the baseline using three different scenarios of economic growth: baseline, moderate, and optimistic. Method of Almost Ideal Demand System (AIDS) was implemented to estimate changes of food consumption. Susenas data from 2017 is used as the baseline of food demand model. Susenas data from 1990–2016 is used to analyze selected food consumption trends and the relationship between food consumption, price trends, and income in all 33 provinces of Indonesia. The results show that future food demand in Indonesia is determined by existing demand, income, price and its composition, and various other factors that affect the behavior and trends of consumption. The policy should focus on the balance between demand-side management and supply-side or productivity improvement, as the majority of food production centers are located in Java.